DAMPAK PRIMA TANI TERHADAP PEMANFAATAN DAN PRODUKTIVITAS SUMBERDAYA LAHAN DAN PENDAPATAN RUMAH TANGGA PETANI - Kasdi Subagyono; Ketut Kariyasa (Balai Besar Pengkajian dan Pengembangan Teknologi Pertanian, 2012)
Impact of Prima Tani on Land Resources Utilization and Productivity and Farmer Household Income. In efforts to accelerate technology adoption and innovation at farmer level, Department of Agriculture through IAARD since 2005 has developed Prima Tani Program that spread over in 25 provinces and at 33 villages. In 2008, it covered 201 villages and 200 districts in all provinces of Indonesia. The aim of this study at assessing the impact of Prima Tani focused on land resources utilization and farmer household income. Study was conducted in West Java (Karawang and Garut districts), as one of province for Prima Tani development. The study results indicate that the Prima Tani had a positive impact on the utilization of land resources. This was evident in the increasing use of land resources for farming activities (13.72%) and cropping intensity index (50-100%). Furthermore, it was also able to significantly improve the land resources productivity (>40%) and enhance the role and contribution of agriculture to farmer household income (33% to 38%). Thus, Prima Tani Program has shown good performance and it it was be in line with government's program in reduction of poverty and unemployment problems in rural areas. Therefore, the success of this program in the future will be determined by the support of various parties and related agencies in encouraging the acceleration of its adoption in broader areas. Dalam upaya mempercepat adopsi dan teknologi inovasi di tingkat petani, Departemen Pertanian melalui Badan Litbang Pertanian sejak 2005 mengembangan Program Prima Tani yang tersebar di 25 provinsi dan 33 desa. Pada 2008, program ini telah tersebar di 201 desa dan 200 kabupaten di seluruh provinsi di Indonesia. Tujuan studi ini adalah mengkaji dampak Prima Tani yang difokuskan pada pemanfaatan sumberdaya lahan dan pendapatan rumah tangga petani. Kajian telah dilakukan di Jawa Barat (Kabupaten Karawang dan Garut), sebagai salah satu provinsi pengembangan Prima Tani. Hasil kajian menunjukkan bahwa Prima Tani mempunyai dampak positif terhadap pemanfaatan sumberdaya lahan. Hal ini dibuktikan semakin meningkatnya penggunaan sumberdaya lahan untuk kegiatan usahatani (13,72%) dan intensitas pertanaman (50-100%). Lebih lanjut, program ini juga secara nyata mampu memperbaiki produktivitas sumberdaya lahan (>40%) dan meningkatkan peranan serta kontribusi usaha pertanian terhadap pendapatan keluarga petani (33% menjadi 38%). Dengan demikian, program yang berawal dari desa ini telah menunjukkan kinerja secara baik dan sejalan dengan program pemerintah untuk mengurangi kemiskinan dan pengangguran di perdesaan. Oleh karena itu, kesuksesan program ini ke depan sangat ditentukan adanya dukungan berbagai pihak dan instansi terkait dalam mendorong percepatan adopsinya dalam skala yang lebih luas.